The Phenomenon of the Sakinah Family in the Rahmat Pura Wedding Tradition - Afabih, Abdillah; Anwar, Khoirul (Al-Mujtahid: Journal of Islamic Family Law, 2024)
The purpose of this paper is three. First, to describe the phenomenon of the Sakinah family in Sumber Pendidikan Mental Agama Allah (SPMAA) Islamic boarding school. Second, it explains the efforts of the executors and participants of the Rahmat Pura wedding tradition in creating a Sakinah family. Third, explain the challenges and solutions the organizers and participants face in realizing this goal. The aspiration for a harmonious family is a shared desire among married couples, including those in arranged marriages. One particular tradition that exemplifies this phenomenon is the Rahmat Pura wedding tradition, which takes place within the context of a pesantren. By applying a phenomenological approach, this article concludes two things. First, the phenomenon of the Sakinah family at SPMAA adheres to the concept of the Sakinah of the Prophets, which is synonymous with the simplicity and struggle of God's religion. Second, among the implementing efforts is to provide providers with pre-marital activities and create a family feeling in the pesantren environment. Meanwhile, the efforts of the participants are to support each other and remind the couple that the purpose of their marriage is the struggle for Allah's religion.